Blockade of Transient Receptor Potential Vanilloid 4 Enhances Antioxidation after Myocardial Ischemia/Reperfusion. (16th June 2019) - Wu, Qiongfeng; Lu, Kai; Zhao, Zhaoyang; Wang, Binbin; Liu, Huixia; Zhang, Shaoshao; Liao, Jie; Zeng, Yu; Dong, Qian; Zhao, Ning; Han, Bing; Du, Yimei
Abstract : Antioxidative stress provides a cardioprotective effect during myocardial ischemia/reperfusion (I/R). Previous research has demonstrated that the blockade of transient receptor potential vanilloid 4 (TRPV4) attenuates myocardial I/R injury. However, the underlying mechanism remains unclear. The current study is aimed at investigating the antioxidative activity of TRPV4 inhibition and elucidating the underlying mechanisms in vitro and ex vivo . We found that the inhibiting TRPV4 by the selective TRPV4 blocker HC-067047 or specific TRPV4-siRNA significantly reduces reactive oxygen species (ROS) and methane dicarboxylic aldehyde (MDA) levels in H9C2 cells exposed to hypoxia/reoxygenation (H/R). Meanwhile, the activity of antioxidative enzymes, particularly superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), is enhanced. Furthermore, after H/R, HC-067047 treatment increases the expression of P-Akt and the translocation of nuclear factor E2-related factor 2 (Nrf2) and related antioxidant response element (ARE) mainly including SOD, GSH-Px, and catalase (CAT). LY294002, an Akt inhibitor, suppresses HC-067047 and specific TRPV4-siRNA-induced Nrf2 expression and its nuclear accumulation. Nrf2 siRNA attenuates HC-067047 and specific TRPV4-siRNA-induced ARE expression. In addition, treatment with LY294002 or Nrf2 siRNA significantly attenuates the antioxidant and anti-injury effects of HC-067047 in vitro . Finally, in experiments on isolated rat hearts, we confirmed the antioxidative stress roles of TRPV4 inhibition during myocardial I/R and the application of exogenous H2 O2 . In conclusion, the inhibition of TRPV4 exerts cardioprotective effects through enhancing antioxidative enzyme activity and expressions via the Akt/Nrf2/ARE pathway.